2010
DOI: 10.1117/12.851574
|View full text |Cite
|
Sign up to set email alerts
|

Design and simulation of programmable relational optoelectronic time-pulse coded processors as base elements for sorting neural networks

Abstract: In the paper we show that the biologically motivated conception of time-pulse encoding usage gives a set of advantages (single methodological basis, universality, tuning simplicity, learning and programming et al) at creation and design of sensor systems with parallel input-output and processing for 2D structures hybrid and next generations neurofuzzy neurocomputers. We show design principles of programmable relational optoelectronic time-pulse encoded processors on the base of continuous logic, order logic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Also, in the study of CNN AlexNet found that the number of layers -25 is not enough to achieve accuracy in the classification of the test group at least up to 80%. In the future, it is proposed to use software and hardware of artificial intelligence, which are discussed in [13,14,15], which will help improve the proposed approach and increase the speed and reliability of diagnosing ultrasound medical images of hip dysplasia.…”
Section: Experimental Research and Comparison Of Modeling Resultsmentioning
confidence: 99%
“…Also, in the study of CNN AlexNet found that the number of layers -25 is not enough to achieve accuracy in the classification of the test group at least up to 80%. In the future, it is proposed to use software and hardware of artificial intelligence, which are discussed in [13,14,15], which will help improve the proposed approach and increase the speed and reliability of diagnosing ultrasound medical images of hip dysplasia.…”
Section: Experimental Research and Comparison Of Modeling Resultsmentioning
confidence: 99%